Ancillary Investigative Tools to Diagnose Fistula in Ano - Dwivedi, Dr.A.K. (International Journal of Psychosocial Rehabilitation, 2020)
Inadequate drainage or spontaneous bursting of a perianal abscess leading to the development of Fistula in ano. If the surgeon fails to track the tract during surgery or inadequate extinction of infection causing the recurrence of the disease. Preoperative imaging is a useful tool for the identification of infection that would have otherwise gone unidentified. Current updates on diagnostic tools recommend that magnetic resonance (MR) imaging outcomes have been considered to impact surgery and noticeably reduce the chances of reappearance. But in countries like India this is not possible for common patients to afford MR imaging because of cost effectiveness and availability of MRI equipment at various remote centres. Other diagnostic techniques like Endoanal and Transcutaneous perianal ultrasonography is also being widely used but this has also got limitations like difficult to use in perianal inflammatory conditions, anal stricture or stenosis and always cannot be done because of many reasons. Hence fistulography is commonly used for preoperative imaging of fistula in ano. In this article, fistula in ano and its various diagnostic techniques are described in detail.